Dr. Kristina Tansavatdi — Deep Plane Facelift — Westlake Village - Tansavatdi, Kristina (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Kristina Tansavatdi, practicing in Westlake Village, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003022; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; westlake village